Hubungan Asupan Mikronutrien dengan Kejadian Diabetes Melitus Tipe 2 pada Dewasa di Wilayah Kerja Puskesmas Mojo Surabaya: Relationship between Micronutrient Intake and the Incidence of Type 2 Diabetes Mellitus among Adults in Mojo Public Health Centre Surabaya - Kamila, Salwa Naura; Sumarmi, Sri (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2025)
Type 2 Diabetes Mellitus is a health problem that has long-term impacts, causing damage to blood vessels in the liver, eyes, kidneys, and nerves. The mechanism of type 2 diabetes is caused by two main factors: imperfect insulin secretion by pancreatic β-cells and the inability of insulin-sensitive tissues to respond to insulin. The risk of type 2 diabetes increases with age. However, the onset of type 2 diabetes now occurs earlier in individuals, starting at the age of twenty. In addition to the effects of high sugar consumption, micronutrient deficiencies are also a factor in the occurrence of type 2 diabetes. Micronutrients play a role in increasing the work of the insulin hormone in regulating blood sugar in the body. This study aims to analyze the relationship between micronutrient intake and the incidence of type 2 diabetes in adults in the Mojo Health Center work area, Surabaya. This study employs a case-control study design with a sample size of 33 respondents for each case and control group, resulting in a total of 66 respondents. Data collection was carried out using an SQ-FFQ. Random blood sugar level data were obtained through blood tests with a glucometer. Data analysis was carried out using the Chi-square correlation test. The results show that there is a relationship between zinc intake (p=0.014; OR=4.025) and manganese (p=0.049; OR=3.316) with the incidence of type 2 diabetes. There is no relationship between selenium intake (p=1.000) and chromium intake (p=1.000) with the incidence of type 2 diabetes. Based on the results of the study, it can be concluded that insufficient zinc intake increases the risk of type 2 diabetes 4.025 times, and insufficient manganese intake increases the risk of type 2 diabetes 3.316 times. Diabetes mellitus patients can consume foods containing high levels of zinc and manganese, such as shellfish, beef, nuts, milk, eggs, and brown rice in an effort to reduce the severity of the disease.